Soil organic matter and physical attributes affected by crop rotation under no-till - Garcia, Rodrigo Arroyo; Li, Yuncong; Rosolem, Ciro Antonio [UNESP] (Wiley, 2013)
Growing cover crops in systems under no tillage affects different pools of soil organic matter, and eventually soil physical attributes are modified. The objective of this study was to evaluate changes in soil organic matter and their relationship with soil physical attributes as affected by plant species grown in rotation with soybean [Glycine max (L.) Merr.] under no-till for 3 yr. Crop rotations included grain sorghum [Sorghum bicolor (L.) Moench], ruzigrass [Urochloa ruziziensis (R. Germ, and CM. Evard) Crins] and sorghum mixed with ruzigrass, all grown in fall/winter, followed by pearl millet [Pennisetum americanum (L.) Leeke], sunn hemp (Crotalaria juncea L.) and sorghum-sudangrass [S. bicolor × S. sudanense (Piper) Stapf] grown during the spring, plus a fallow check plot. Soybean was grown as the summer crop. Millet and sorghum-sudangrass cropped in spring showed higher root and shoot production as spring cropping. In fall/winter, sorghum mixed with ruzigrass yielded higher phytomass compared with sole cropping. Soil physical attributes and organic matter fractioning were positively affected by cropping millet and sorghum-sudangrass whereas intermediate effects were observed after sunn hemp. Maintaining fallow in spring had negative effects on soil organic matter and physical properties. Ruzigrass and sorghum mixed with ruzigrass cropped in fall/winter resulted in better soil quality. Spring cover crops were more efficient in changing soil bulk density, porosity, and aggregates down to 0 to 10 cm; on the other hand, fall/winter cropping showed significant effects on bulk density in the uppermost soil layer. Total C levels in soil were increased after a 3-yr rotation period due to poor initial physical conditions. Fractions of particulate organic C, microbial C, and C in macroaggregates were the most affected by crop rotations, and showed high relation with improved soil physical attributes (porosity, density, and aggregates larger than 2 mm). © Soil Science Society of America, All rights reserved.